Ultrasound evaluation in follow-up of urate-lowering therapy in gout: the USEFUL study. (4th October 2018) - Ebstein, Esther; Forien, Marine; Norkuviene, Eleonora; Richette, Pascal; Mouterde, Gaël; Daien, Claire; Ea, Hang-Korng; Brière, Claire; Lioté, Frédéric; Petraitis, Mykolas; Bardin, Thomas; Ora, Jérémy; et al.
Abstract: Objectives: We aimed to determine the ability of ultrasonography (US) to show disappearance of urate deposits in gouty patients requiring urate-lowering therapy (ULT). Methods: We performed a 6-month multicentre prospective study including patients with: proven gout; presence of US features of gout (tophus and/or double contour sign) at the knee and/or first metatarsophalangeal joints; and no current ULT. US evaluations were performed at baseline and at months 3 and 6 (M3, M6) after starting ULT. Outcomes were: the change in US features of gout at M6 according to final (M6) serum urate (SU) level (high, > 360 μmol/l, i.e. > 6 mg/dl; low, 300–360 μmol/l, i.e. 5-6 mg/dl; very low, < 300 μmol/l, i.e. < 5 mg/dl); and correlation between changed US features and final SU level. Results: We included 79 gouty patients (mean ± s .d ., age 61.8 (14) years, 91% males, disease duration 6.3 (6.1) years). Baseline SU level was 530 ± 97 µmol/l (i.e. 8.9 mg/dl ± 1.6mg/dl). At least one US tophus and double contour sign was observed in 74 (94%) and 68 (86%) patients, respectively. Among the 67 completers at M6, 18 and 39 achieved a very low and low SU level, respectively. We found a significant decrease in US features of gout among patients with the lowest SU level ( P < 0.001). Final M6 SU level was positively correlated with decreased size of tophus (r = 0.54 [95% CI: 0.34, 0.70], P < 0.0001), and inversely correlated with proportion of double contour sign disappearance (r=−0.59 [−0.74, −0.40]). Conclusion: US can show decreased urate deposition after ULT, which is correlated with decreased SU level. The responsiveness of US in gout is demonstrated and can be useful for gout follow-up and adherence to ULT.